2016
DOI: 10.1016/j.invent.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting for health, medical or psychosocial research using Facebook: Systematic review

Abstract: Recruiting participants is a challenge for many health, medical and psychosocial research projects. One tool more frequently being used to improve recruitment is the social networking website Facebook. A systematic review was conducted to identify studies that have used Facebook to recruit participants of all ages, to any psychosocial, health or medical research. 110 unique studies that used Facebook as a recruitment source were included in the review. The majority of studies used a cross-sectional design (80%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
299
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(330 citation statements)
references
References 110 publications
18
299
2
2
Order By: Relevance
“…Data were collected through social media and e-mail snowballing. These methods have proven to be effective and cost-efficient in previous studies (for systematic reviews see Thornton et al, 2016;Topolovec-Vranic & Natarajan, 2016). A total pool of 2,698 responses was collected, most of which were from women (67.6% of the respondents).…”
Section: Methods Samplementioning
confidence: 99%
“…Data were collected through social media and e-mail snowballing. These methods have proven to be effective and cost-efficient in previous studies (for systematic reviews see Thornton et al, 2016;Topolovec-Vranic & Natarajan, 2016). A total pool of 2,698 responses was collected, most of which were from women (67.6% of the respondents).…”
Section: Methods Samplementioning
confidence: 99%
“…However, the costs of hiring research staff with language abilities to distribute flyers and screen potential participants is likely more expensive and timeintensive than the minimal time and personnel needed for recruitment through Facebook. Although we cannot speculate on the demographic similarities or differences between the East Asian and Latinx cancer survivors recruited through Facebook or in person, a growing number of studies have found minimal differences between participants recruited online or in person [11]. Yet, the feasibility and effectiveness of recruiting through other social media platforms (e.g., Craigslist) requires future testing.…”
Section: Limitationsmentioning
confidence: 91%
“…The ads shown on Facebook were approved by the Institutional Review Board. Following the recommendations by Thornton and colleagues [11], the ads were concise, showed that the research study was affiliated with a university, and offered incentives for participation (see Figure 1). The link in each Facebook ad was connected to the study website, which stated the eligibility criteria for participating in the 30-minute online survey in the respective language that the ads were clicked (e.g., clicking the Korean ad would lead to the study information presented in Korean).…”
Section: Facebook Adsmentioning
confidence: 99%
See 2 more Smart Citations